2010
DOI: 10.1007/s11192-010-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

A journal co-citation analysis of library and information science in China

Abstract: This paper aims to reveal the relationship and structure of library and information science (LIS) journals in China. 24 core LIS journals in China are selected and the relevant data of journal co-citation are retrieved from Chinese Journal Full-Text Database constructed by China National Knowledge Infrastructure during the period of 1999-2009. By calculating mean co-citation frequencies and correlation coefficients, we find that there is a strong relationship among LIS journals in China. Utilizing the methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 15 publications
1
41
0
3
Order By: Relevance
“…Humanity orientation in digital libraries research in China is mainly driven by library science, which mainly deals with problems about people's rights or benefits in digital libraries environments. Such studying result also reveals the research characteristics of Chinese library science in digital environments, which is more or less consistent with the research done by Hu et al 2010, having concluded that Chinese library and information science (LIS) journals with more research topics of computers and information technology are on the left part of MDS analysis map, while those with more research topics of theory and practice in library and information science (LIS) are scattered on the right part of MDS analysis map.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Humanity orientation in digital libraries research in China is mainly driven by library science, which mainly deals with problems about people's rights or benefits in digital libraries environments. Such studying result also reveals the research characteristics of Chinese library science in digital environments, which is more or less consistent with the research done by Hu et al 2010, having concluded that Chinese library and information science (LIS) journals with more research topics of computers and information technology are on the left part of MDS analysis map, while those with more research topics of theory and practice in library and information science (LIS) are scattered on the right part of MDS analysis map.…”
Section: Discussionsupporting
confidence: 84%
“…1, because keywords of technology orientation just occupy relatively marginal positions, but keywords of humanity orientation occupy relatively predominant positions, just as conclusion in the paper written by Hu et al 2010 that the integrated tendency of Library Science and Information Science in China are getting more and more obvious, but the development is not balanced as a whole, because Library Science occupies the dominant position.…”
Section: Discussionmentioning
confidence: 99%
“…The co-citation analysis methods that CiteSpace provides are document co-citation analysis (Chen 2006;Leydesdorff 2005), author co-citation analysis (Chen and Carr 1999;Nerur et al 2008;White and McCain 1998) and journal co-citation analysis (Hu et al 2011;Liu 2005;Tsay et al 2003). These methods complement each other.…”
Section: Introductionmentioning
confidence: 99%
“…Quant à l'interdisciplinarité, notre corpus confirme au niveau des revues ce qu'une recherche dans les bases de données scientométriques 12 montre au niveau des articles : contrairement à d'autres disciplines, une partie significative des publications du domaine ICD est diffusée dans des revues multidisciplinaires ou appartenant à d'autres disciplines. C'est un fait, ce n'est pas un problème en soi.…”
Section: /15unclassified
“…Mais les publications d'autres disciplines -et pas seulement en sciences médicales ou sciences de la vie -sont mieux représentées dans les outils scientométriques. En ce qui concerne les SHS en France, les 12 Un exemple (juin 2011) : en recherchant les articles indexés sous le mot-clé scientometrics, Scopus identifie 222 références publiées depuis 2000. Parmi ces références, 114 articles (51,4%) sont publiés dans des revues en dehors du champ ICD.…”
Section: Francophonie Et Internationalitéunclassified